Sport participation, acculturative stress, and depressive symptoms among international college students in the United States - Yim, Hyosoon; Kim, Amy Chan Hyung; Du, James; James, Jeffrey D. (Frontiers in Psychiatry, 2023)
Introduction The distinctive social nature of sport in its capacity to promote immigrants’ adaptation to the new society has been regarded as a vehicle to cope with adverse mental health outcomes derived from acculturative stress (AS) and feelings of marginalization. However, the evidence on the relationship between sport participation (SP), AS, and mental health have been lacking and fragmented. Recognizing this challenge, we examined the mediating effect of AS on the relationship between SP and depressive symptoms (DS) among international college students in the USA. Methods A total of 203 international college students in the USA were recruited via Prolific. The instrumentation included previously validated measures: SP (SLIM-18), AS (ASSIS), DS (CES-D-10), sense of coherence (SOC-13), and demographic characteristics. Results Mediation analysis showed a significant association between (1) SP and DS (ß = −0.030, p < 0.05) and (2) AS and DS (ß = 0.053, p < 0.001), while (3) no significant indirect effect of AS was found [ß = −0.001, SE = 0.0003, 95% CI (−0.008, 0.004)]. Discussion Even though several previous scholars have argued that SP is an effective tool to cope with AS among international students, the present study implies this may not be applied to all international students. Specifically, AS and DS among European participants were lower than those from non-European countries, including Asia. Future studies using meta-analysis could be beneficial to examine the external validity of the previous studies on the relationship between SP, acculturation, and mental health to address this potential heterogeneity on the level of AS based on their origin countries or continents. The current study provides meaningful implications for adopting the transformative marketing perspective, which is a marketing approach that pursues positive social outcomes by promoting positive behavior of the target population.